The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s11606-013-2577-z
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Harmful and Hazardous Alcohol Consumption in Older U.S. Adults: Data from the 2005–2008 National Health and Nutrition Examination Survey (NHANES)

Abstract: BACKGROUND: Alcohol consumption and its interaction with disease, medication use, and functional status may result in serious health problems, but little information exists about the national prevalence of alcohol-related health risk in older adults. OBJECTIVE: To estimate the prevalence of harmful and hazardous alcohol use and the prevalence of consumption in excess of National Institute of Alcohol Abuse and Alcoholism (NIAAA) recommendations, in people aged 65 and older, and by sex and race/ethnicity sub-gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 27 publications
(20 reference statements)
0
48
0
1
Order By: Relevance
“…20 Older adults with health problems tend to reduce substance use, and ex-drinker older adults tend to include "sick quitters" who may have quit drinking due to health/mental health and alcoholrelated problems over the course of their lives 21 However, significant numbers of older adults continue to engage in harmful/hazardous drinking behaviors. 22 Given aging-and disease-related physiological changes, even relatively low levels of alcohol or drug use may exacerbate health and MH problems in older adults. [23][24][25] Alcohol-and drug-related problems that do not meet SUD criteria may also pose barriers to seeking MH services as older adults may use these substances to cope with MH problems, and substance use/ misuse can compromise MH treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…20 Older adults with health problems tend to reduce substance use, and ex-drinker older adults tend to include "sick quitters" who may have quit drinking due to health/mental health and alcoholrelated problems over the course of their lives 21 However, significant numbers of older adults continue to engage in harmful/hazardous drinking behaviors. 22 Given aging-and disease-related physiological changes, even relatively low levels of alcohol or drug use may exacerbate health and MH problems in older adults. [23][24][25] Alcohol-and drug-related problems that do not meet SUD criteria may also pose barriers to seeking MH services as older adults may use these substances to cope with MH problems, and substance use/ misuse can compromise MH treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…2 2 In the context of drug consumption, the media is indicated as a contributory factor for the naturalization of alcohol consumption, as revealed by the following statements:…”
Section: It Is So Common That You Do Not Treat Alcohol Itself As a Dmentioning
confidence: 99%
“…2 2 The speeches also highlight the concern about alcohol consumption, as it is considered a gateway to other drugs. 1 In general, the descriptions reveal the complexity of the alcohol consumption phenomenon, whose influence is the sociocultural, political, economic, ethical-legal context, among other dimensions.…”
Section: The Naturalization Of Alcohol Is Coming Into Our House Thromentioning
confidence: 99%
See 1 more Smart Citation
“…1 Based on the amount consumed, they found that 15 % of older drinkers exceeded recommended limits, but when other health characteristics were taken into account, drinking was potentially harmful in over one-third of those who drank. Wilson's findings are not new; they are similar to results reported in previous studies that included both the amount and the subject's health characteristics in judging the healthiness of drinking.…”
mentioning
confidence: 99%